2016
DOI: 10.3389/fnagi.2016.00288
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Activity Changes after 4 Weeks Supplementation with a Multi-Vitamin/Mineral Combination: A Randomized, Double-Blind, Placebo-Controlled Trial Exploring Functional Magnetic Resonance Imaging and Steady-State Visual Evoked Potentials during Working Memory

Abstract: This study explored the neurocognitive effects of 4 weeks daily supplementation with a multi-vitamin and -mineral combination (MVM) in healthy adults (aged 18–40 years). Using a randomized, double-blind, placebo-controlled design, participants underwent assessments of brain activity using functional Magnetic Resonance Imaging (fMRI; n = 32, 16 females) and Steady-State Visual Evoked Potential recordings (SSVEP; n = 39, 20 females) during working memory and continuous performance tasks at baseline and following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Specifically, the quality and magnitude of the activation pattern, rather than the behavioural outcomes, may be differentially susceptible to change. This is consistent with previous findings using the same task following 30‐day administration of cocoa flavanols in a similar population (Camfield et al, 2012) and a 28‐day multivitamin intervention in a healthy young adult cohort (White et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, the quality and magnitude of the activation pattern, rather than the behavioural outcomes, may be differentially susceptible to change. This is consistent with previous findings using the same task following 30‐day administration of cocoa flavanols in a similar population (Camfield et al, 2012) and a 28‐day multivitamin intervention in a healthy young adult cohort (White et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Two cognitive tasks were completed during SSVEP recording, an AX‐CP task (AX‐CPT) and a SWM, see for details. These two tasks have been utilised in a series of recent trials investigating modulation of SSVEP responses through pharmaceutical (Silberstein, Pipingas, Farrow, Levy, & Stough, 2016) and nutraceutical interventions (Camfield et al, 2012; White et al, 2016, 2017), with the SWM task probing the specific cognitive domain previously impacted by P. quinquefolius (Scholey et al, 2010). Acquisition and pre‐processing of the SSVEP were performed according to White et al (2016; 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the same authors also reported preliminary findings suggesting that this same 4-week multiple micronutrient supplementation could induce changes in brain function, using both hemodynamic and electrophysiological assessments. During working memory tasks, the centro-parietal regions showed higher activity after multiple supplementation, especially when subjects were investigated in a situation of mental fatigue [221]. The enhanced benefit of supplementation for subjects with low vitamin status at baseline is supported, for example, by the results of a 13 years supplementation trial of B vitamins (B6 + B9 + B12) in which cognitive function was assessed in women with a high cardiovascular risk.…”
Section: Effect Of Supplementation With Multiple Micronutrients On Mementioning
confidence: 99%
“…Our 14-day food capture window was twice the length of most studies—that use a much smaller timeframe to capture general eating habits (typically 3–7 days, Hughes et al, 2012; White et al, 2016; Zweers et al, 2018), although our methods are similar in other respects. There was no need to repeat this, unlike physiological measures because participants were instructed to follow their normal dietary pattern (indeed this instruction was likely superfluous because it is incredibly difficult to get people to change their eating habits).…”
Section: Methodsmentioning
confidence: 99%